1995
DOI: 10.2151/jmsj1965.73.6_1029
|View full text |Cite
|
Sign up to set email alerts
|

General Aspects of Land and Sea Breezes in Osaka Bay and Surrounding Area

Abstract: The general aspects of land and sea breezes in the Osaka Bay area and its environment are revealed from an analysis of the wind data obtained by the AMeDAS. The study area consists of a complex land-sea configuration and a complex topography which includes plains, hilly terrain, and mountainous regions. The land and sea breezes are classified into five types according to the behavior of the sea breeze at several locations in the study area.The most frequently occurring type is characterized in the following. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The PW is important in determining whether or not a sea breeze will be detectable on land (a very strong offshore PW will prevent the SBC from reaching the coast), as well as exerting an influence on its behavior [e.g., Finkele et al ., 1995]. Mizuma 's [1995, 1998] observational studies of SBC behavior on the coast of Japan include descriptions of several manually identified sea breeze modes, which are dependent on the shape of the local coastline and the direction and strength of the PW. Several other studies have examined SBC response to the PW both generically and along specific coastlines [e.g., Fisher , 1960; Estoque , 1962; Pearson et al ., 1983; McKendry and Roulet , 1994; Planchon and Cautenet , 1997; Melas et al ., 1998; Asimakopoulos et al ., 1999; Clappier et al ., 2000; Melas et al ., 2000; Laird and Kristovich , 2001; Oliphant et al ., 2001; Lericos et al ., 2002].…”
Section: Modern Understandingmentioning
confidence: 99%
“…The PW is important in determining whether or not a sea breeze will be detectable on land (a very strong offshore PW will prevent the SBC from reaching the coast), as well as exerting an influence on its behavior [e.g., Finkele et al ., 1995]. Mizuma 's [1995, 1998] observational studies of SBC behavior on the coast of Japan include descriptions of several manually identified sea breeze modes, which are dependent on the shape of the local coastline and the direction and strength of the PW. Several other studies have examined SBC response to the PW both generically and along specific coastlines [e.g., Fisher , 1960; Estoque , 1962; Pearson et al ., 1983; McKendry and Roulet , 1994; Planchon and Cautenet , 1997; Melas et al ., 1998; Asimakopoulos et al ., 1999; Clappier et al ., 2000; Melas et al ., 2000; Laird and Kristovich , 2001; Oliphant et al ., 2001; Lericos et al ., 2002].…”
Section: Modern Understandingmentioning
confidence: 99%
“…The southerly wind termed the "ocean wind" in the Kinki district , mentioned by Itoh and Noda (1989), may be the same kind of wind system as the ESB in the Kanto plain from the viewpoint of the inducing mechanism. From wind distribution maps presented by Itoh (1995) and Mizuma (1995), an ESB-like surface airflow pattern can be seen over the Kinki dis trict. The ESB and its relation to the pressure field over the Nobi plain were described by Mori et al (1994).…”
Section: Extended Sea Breezementioning
confidence: 94%
“…Diurnal variations in ground temperature, static stability, Coriolis force, prevailing wind, and topography including the size and shape of land and coastline also affect the development of sea/land breeze (Simpson 1994). Mizuma (1995Mizuma ( , 1998 has described the sea/land-breeze system in the Seto Inland Sea, but did not pay attention to either the spatial structure of the sea/land breeze offshore or the influence of the SST front on the sea/land-breeze system in the Seto Inland Sea.…”
Section: Introductionmentioning
confidence: 99%